Optimizing the Productivity and Quality of Rambak Pisang Based on Automatic Oil Draining Machine Technology (Spinner) at MSME Kartika Kencana Wonosari District - Faiz, Mohamad Rodhi; Arif Nur Afandi; Sujito, Sujito; Hari Putranto; Abdullah Iskandar Syah; Shandy Krisnawan (Khidmatuna (Jurnal Pengabdian Kepada Masyarakat), 2023)
This community service program aims to apply appropriate technology in the form of a banana rambak automatic draining machine (Spinner) to increase the business productivity of banana rambak business actors in Wonoagung Village, Kasembon District, Malang Regency. The banana rambak automatic oil draining machine (Spinner) was designed because business actors get a problem in the production process, especially in the process of draining business actors still use traditional techniques, namely placed in a container and given a paper base and then aerated. Thus, business actors must take a long time in the process of draining the oil in banana rambak. This can hinder productivity for banana rambak business actors so that banana rambak products have low quality. The application of the spinner machine aims to facilitate and accelerate the business actors belonging to the Kartika Kencana MSME in producing banana rambak. Thus, business actors have quality productivity and can increase productivity, especially banana rambak processing.